Fresh fly fabulous 50 years of hip hop style - Way, Elizabeth; Romero, Elena 1973; Rick Slick 1965- (Rizzoli Electa in association with The Museum at FIT, 2023)
"Fresh Fly Fabulous is the definitive source for hip hop style, brought to life by the groundbreaking photographers who captured it firsthand, including Janette Beckman, Jamel Shabazz, and Ernie Paniccioli."--
"Published on the occasion of the exhibition: Fresh Fly Fabulous: 50 Year of Hip Hop Style organized by The Museum at FIT ... [at] The Museum at FIT, New York, February 8-April 23, 2023"--Colophon
Keywords: Hip-hop / Influence / Clothing / United States / Exhibitions; Hip-hop dance / United States / Exhibitions; Fashion / United States / 20th century / Exhibitions; Fashion / United States / 21st century / Exhibitions; Fashion / African American influences / History / 20th century / Exhibitions; Hip-hop / United States / Influence / Exhibitions; Hip-hop / United States / Exhibitions; Hip-hop / Social aspects / United States / Exhibitions; Hip-hop (Danse) / États-Unis / Expositions; Hip-hop / États-Unis / Expositions; Hip-hop / Aspect social / États-Unis / Expositions; Fashion; Fashion / African American influences; Hip-hop; Hip-hop / Influence; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; 1900-2099; Exhibition catalogs; exhibition catalogs; History; Catalogues d'exposition; Ausstellungskatalog -- The Museum at FIT -- 08.02.2023-23.04.2023 -- New York